Heat-Flux Effect on Fluid Flow and Convective Heat Transfer through a Rotating Curved Micro-Channel (Journal of Science and Technology Research, 2023)
The present paper investigates heat-flux effect and the dissemination of energy in a rotating bent square micro-channel (MC) subject to a temperature gradient between the vertical sidewalls. The flow structure prevailing the problem is solved by applying a highly accurate spectral-based numerical scheme. The flow controlling parameters are the Dean number (0